(untitled) (Dhaka University Journal of Science, 2019)
Better child health can be guaranteed by ensuring postnatal care for the newborns after birth. Newborns in the slums of Bangladesh are lagging behind to receive postnatal care and the percentage of newborns receiving health check-up from medically trained provider within first two months after birth is very low. The purpose of this study is to find out the potential determinants of receiving postnatal care from medically trained provider for slum newborns in Bangladesh. Data have been extracted from Bangladesh Urban Health Survey (UHS), 2013 to serve the purpose of the study. From regression analysis, it is found that antenatal care during pregnancy from medically trained provider, delivery by skilled birth attendant, economic status of the newborn family, education level and media exposure of mothers are significant factors associated with the uptake of postnatal care from medically trained provider for the newborns in slums. Dhaka Univ. J. Sci. 67(1): 69-72, 2019 (January)